Cinética e pirólise do óleo de licuri (Syagrus coronata) utilizando vermiculita sódica/ácida com óxido de zinco para obtenção de bio-óleo - Oliveira, João Leonardo Freitas (2019)
The use of fuels derived from non-renewable sources, such as oil, in recent decades has caused major changes in the climate with global warming. Dependence on fossil energy sources is still the major challenge for researchers and new generations, in 2015 several countries signed the Paris agreement with targets for carbon dioxide reduction, which is the starting point for new public policies with incentives for production of biofuels around the world. In this work, the licuri oil (Syagrus coronata) was used as a renewable source for the production of hydrocarbon-rich bio-oil, for which sodium and acid vermiculite were used as catalysts and catalytic support for zinc oxide, conducting studies of conversion and final deoxygenation of the oil. In all, six catalysts were synthesized, zinc oxide (ZnO), sodium vermiculite supported with zinc oxide in mass percentages of 1 and 6% (VZn1 and VZn6), sodium vermiculite (V) and acid vermiculite with 1% and 6% % zinc oxide, VaZn1 and VaZn6, respectively. The catalysts under study were characterized by the following techniques: X-ray diffractometry (XRD), Thermogravimetric Analysis (TGA), Nitrogen Adsorption/Desorption, Scanning Electron Microscopy (SEM) and X-ray Fluorescence (FRX). The pyrolysis tests for the determination of activation energy were carried out on a thermogravimetric scale following the Kissinger-Akahira-Sunose (KAS) and Ozawa Flynn-Wall (OFW) kinetic models. The rapid pyrolysis was carried out using a pyrolyzer coupled to the injection system of a gas chromatograph with mass detector (Py-CG/MS) for separation and determination of the bio-oil composition. In the kinetic study of the pyrolysis of the licuri oil, the catalysts that presented the highest catalytic activity were V, VZn1 and VaZn1, presenting activation energy lower than the thermal pyrolysis of the oil from the conversion of 10%. VZn1 and VaZn1 presented higher activity for the formation of hydrocarbons by deoxygenation of the oil, with hydrocarbons formed predominantly in the kerosene range with 53,5% (C11-C16) for catalysts with sodium vermiculite and in the gasoline range with 39,7% (C5-C10) and with 41,8% (C16-C24) with the use of VaZn1, showing that the zinc oxide associated with vermiculite presents as an alternative to conventional catalysts for studies in the area of pyrolysis and production of biooil from the licuri oil.